2021
DOI: 10.3390/cancers13061354
|View full text |Cite
|
Sign up to set email alerts
|

The Plasma Membrane Ca2+ Pump PMCA4b Regulates Melanoma Cell Migration through Remodeling of the Actin Cytoskeleton

Abstract: We demonstrated that the plasma membrane Ca2+ ATPase PMCA4b inhibits migration and metastatic activity of BRAF mutant melanoma cells. Actin dynamics are essential for cells to move, invade and metastasize, therefore, we hypothesized that PMCA4b affected cell migration through remodeling of the actin cytoskeleton. We found that expression of PMCA4b in A375 BRAF mutant melanoma cells induced a profound change in cell shape, cell culture morphology, and displayed a polarized migratory character. Along with these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 76 publications
1
15
0
Order By: Relevance
“…Our previous preclinical studies indicated a metastasis suppressor function of PMCA4 in melanoma [ 14 , 15 , 16 , 17 ]. Our in silico analysis of a recent large cell line panel with in vivo metastatic potential screen corroborates the putative metastasis suppressor function of PMCA4 [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous preclinical studies indicated a metastasis suppressor function of PMCA4 in melanoma [ 14 , 15 , 16 , 17 ]. Our in silico analysis of a recent large cell line panel with in vivo metastatic potential screen corroborates the putative metastasis suppressor function of PMCA4 [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of this pathway increased the abundance of PMCA4b by increasing its stability [ 16 ]. Finally, PMCA4b was able to inhibit cell migration through the remodeling of the actin cytoskeleton by increasing cell–cell connections as well as lamellipodia and stress fiber formation [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Naffa et al made the interesting observation that PMCA4b can inhibit the migration of BRAF-mutant melanoma cells and impair their metastatic activity [115]. The authors suggest that by remodeling the actin cytoskeleton, PMCA4b affects the cell migration of those cells.…”
Section: Pmca4mentioning
confidence: 99%
“…Melanoma is a classic model to analyze tumor cell migration in clinics and research [ 8 , 9 ] and this collection of Cell Motility and Cancer includes three contributions [ 10 , 11 , 12 ]. An Australian clinical study of 306 metastatic melanomas has found that BRAF + NRAS mutations were associated to the central nervous system and liver metastases, while BRAF mutation was to lymph node metastases and NRAS mutation with lung metastases [ 8 ], so tumor mutation status may advise to direct specifically to these sites the clinical surveillance of these patients.…”
mentioning
confidence: 99%
“…The authors conclude that using Tspan8-blocking antibodies would prevent early melanoma from spreading [ 10 ]. Naffa et al [ 11 ] show that PMCA4b, a plasma membrane Ca 2+ key pump in the regulation of cytosolic Ca 2+ concentration, regulates melanoma cell migration via remodeling the actin cytoskeleton. PMCA4b plays a key role in regulating cell polarity through F-actin rearrangement resulting in a less aggressive phenotype.…”
mentioning
confidence: 99%